Microstructure and fatigue properties of AA2519-O friction stir welded joint. (2020) - Kosturek, Robert; Śnieżek, Lucjan; Torzewski, Janusz; Wachowski, Marcin
Abstract: The aim of this research was to investigate the microstructure and fatigue properties of AA2519-O joint obtained in the friction stir welding process. The microstructure of the joint has been analyzed with the use of a light electron microscope and compared with the results of microhardness analysis. Fatigue properties were established in low-cycle fatigue tests with constant true strain amplitude equal to ε = 0.25%. The obtained amplitudes of stress and plastic strain have been presented in this paper. The fatigue fracture in the tested sample was analyzed with the use of a scanning electron microscope.